Portal vein thrombosis secondary to postoperative gastric cancer: Report of two cases. Issue 3 (October 2020) - Zhang, Zhen; Mei, Yan; Cheng, Haidong; Wu, Xinlin
Few cases of portal vein thrombosis secondary to gastric cancer surgery have been reported. Here we report the diagnosis and management of two such cases. Case 1: Gastric carcinoma with acute hematemesis was detected by endoscopy in the gastric body of a 48-year-old woman. Histologic examination revealed signet-ring cell carcinoma with marked invasion of the vessels and nerves. Laparoscopic partial gastrectomy and Roux-en-Y gastrogastrostomy were performed. One month after surgery, imaging examination showed the formation of thrombi in the main portal vein and the right hepatic vein. Case 2: Gastric carcinoma with pyloric obstruction was clinically diagnosed in a 66-year-old woman. Laparoscopic partial gastrectomy and Billroth Roux-en-Y gastrogastrostomy were again performed. Two months after surgery, an abdominal imaging examination detected a thrombus in the right hepatic vein. Clinicians should consider portal vein thrombosis in patients with hyperthermia combined with an abnormal increase in procalcitonin.